The playground problem - Mcnamara, Margaret (New York : Scholastic, 2004)
When first grades Nick, Jamie and Reza refuse to let emma join their soccer game just because she is a girl, Emma and her father devise a plan to teach the boys a lesson.
"Level 1, starting to read"
Keywords: Sex role-- fiction; Schools-- fiction; Soccer- fiction